Ramification of gum arabic microencapsulation on the physicochemical and microbiological properties of butterfly pea (Clitoria ternatea) flowers using ultrasonic spray drye - Khairi Zainol; H.W. Lew; Zamzahaila Mohd Zin; Shamsul Bahri Abd Razak; Nurmahani M. Maidin; Hasmadi Mamat (2020)
Butterfly Pea (Clitoria ternatea) flower is commonly used to treat various diseases and has long been part of the science of phytomedicines. Ultrasonic assisted extraction technique is a simple, cheap and efficient alternative to traditional extraction methods, producing a much smaller particle size than conventional spray drier. This study was aimed to evaluate the physicochemical and microbiological properties of microencapsulated butterfly pea flower (MEBP) powder prepared using ultrasonic spraying technique. The samples were microencapsulated with different amount of Gum Arabic (GA) (0, 2, 4, 6, 8 and 10%). Surface morphology of the MEBP powder was examined using SEM showed different molecular structures in different MEBP powder. FTIR analysis identified phenolic hydroxyl group (1061.69 cm-1 and 3385.36 cm-1 ), sulfite group (1062.01 cm-1 , 1065.92 cm-1 , 1077.15 cm-1 , 1234.72 cm-1 and 1261.74 cm-1 ) and amide group (1635.99 cm-1 , 1636.74 cm-1 , 1654.14 cm-1 and 3417.2 cm-1 ). 2,2-diphenyl-1 -picrylhydrazyl (DPPH), thiobarbituric acid (TBA), total phenolic content (TPC), total flavonoid content (TFC) found to be ranging from 35.85±0.57 to 130.85±3.00 mg GAE/g dried sample, 4.32±0.04 to 6.90±0.11 mg QE/g dried sample, respectively. It was found that Bacillus cereus was sensitive to MEBP powder as the results showed a prominent inhibition zone (5.67±0.6 mm to 11.67±2.3 mm). MEBP produced with GA 6% ultrasonic spray drier was found to be effective in sustaining its antioxidative activities and the microbial activities were found to be active. This result provided useful information data on the best technique to use ultrasonic spray dryer to retain antioxidant compounds.